Climate Change Response: Evidence from the Margaret River Wine Region of Australia - Galbreath, Jeremy (Wiley Interscience, 2014)
This study explores the relevancy of climate change to business using a sample of wine firms operating in Margaret River, Western Australia, one of the premier wine regions of the world. Using a qualitative approach based on thematic analysis, the results challenge the extent to which climate change is a salient stakeholder, while demonstrating that the phenomenon may, in fact, be beneficial. Response actions towards climate change demonstrate both mitigative and adaptive actions, although differences in their level and rate of implementation appear to be attributable to a mix of normative and instrumental trade-offs. Implications of the findings are discussed, with a particular focus on location theory and economic barriers as a key driver of trade-offs between the choice of mitigative or adaptive response to climate change.